ADVANTAGES AND DISADVANTAGES OF USING DIGITAL LITERACY - Kazakova Dilora Gaffarovna , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Today digital literacy is the most important skill. Properly digitally literate individuals are desperately needed by the general populace, nation builders, and the upcoming techno-age generation. In this day and age, digital literacy is the new life skill. The society as a whole is being affected by the digital environment. All of us can live happily and comfortably only if we are digitally literate to survive in this digital age. Only those who are digitally literate are eligible for the majority of job openings.